Gender Role Inequality in Marginalized Households - Soraya, Ade Ayu; Wijaya, R. Pasifikus Christa; Panis, Marleny Purnamasary (Journal of Health and Behavioral Science, 2025)
Gender inequality remains a pressing social issue, particularly in thedivision of roles between men and women. Among marginalized communities,gender relations are further complicated by intersecting social and economicpressures. This study examines gender role inequality within family life in the AquAda Community, Kupang, employing a qualitative phenomenological approach.Data were gathered through in-depth interviews with 9 participants and analyzedusing Caroline Moser’s gender analysis framework. The findings reveal that womenexperience a double burden, balancing work outside the home with full responsibilityfor domestic tasks. These inequalities are entrenched by strong patriarchal culturalnorms. Economic hardship further exacerbates gender disparities, while maledominance in household decision-making contributes to negative consequences forwomen’s well-being. The study highlights the emergence of awareness and dialogueamong couples regarding the need for more equitable role-sharing, signaling thepotential for gradual transformation in gender relations within marginalizedcontexts.